R.A Kartini's Struggle for Women's Emancipation - Febiyanti, Alisa (SINGOSARI: Jurnal Perkumpulan Prodi Pendidikan Sejarah Se-Indonesia (P3SI) Wilayah Jawa Timur, 2024)
The emancipation of women is often seen as a movement of women's injustice in an effort to seek justice for women. The position of men and women is the same, but often the degree of men is higher than the degree of women. One of the figures who championed women's emancipation or feminism was R.A Kartini, who was a national figure of the Jepara community. Her struggle and role in women's emancipation gave results that can be felt now, namely being able to take an education that is equal to men in terms of obtaining an education. So the author is interested in discussing the role of R.A Kartini in the emancipation of women in Indonesia. This research uses the literacy study method using the research steps of topic selection, heuristics, verification, interpretation, and historiography. The results of the writing show that R.A Kartini played an important role in the emancipation of women, especially in terms of education, especially for women. namely by establishing a “Girl's School” in the Jepara area.